Attitudes, Subjective Norms, Behavior Control, Entrepreneurship Education, Self-Efficacy and Entrepreneurial Intentions of Students Using E-Commerce - Milatul Hasanah; I Ketut Yadnyana (E-Jurnal Akuntansi, 2024)
The research aims to obtain empirical evidence regarding the influence of attitudes, subjective norms, behavioral control, entrepreneurship education and self-efficacy on entrepreneurial intentions to use e-commerce among accounting students. The analysis technique used was multiple linear regression analysis with the sampling method using proportionate stratified random sampling, obtaining a sample of 84 respondents. The results showed that attitude, entrepreneurship education and self-efficacy had a positive and significant effect, while behavioral control had a negative and significant effect on entrepreneurial intentions using e-commerce in accounting students. Subjective norms have no effect on entrepreneurial intentions using e-commerce in accounting students.